Mouse models in burns research: Characterisation of the hypermetabolic response to burn injury. Issue 3 (May 2020) - Hew, Jonathan J.; Parungao, Roxanne J.; Shi, Huaikai; Tsai, Kevin Hung-Yueh; Kim, Sarah; Ma, Duncan; Malcolm, Josephine; Li, Zhe; Maitz, Peter K.; Wang, Yiwei
Highlights: Burn injury induced hypermetabolism in a mouse model. Severe burns resulted in prolonged wound healing, a more pronounced increase in basal energy expenditure. Severe burns triggered a greater stress and systemic inflammatory response. Abstract: Objective: The aim of the study is to characterise burn induced hypermetabolism in a mouse model. Summary Background Data: There are many mouse models of burn injury currently available however, their use in burns research is limited by the general assumption that post-burn hypermetabolism is difficult to study in these models. Methods: Male Balb/c mice were subjected to either a small (1 cm 2 ) or large (4 cm 2 ) contact burn. The hypermetabolic response to burn injury was determined by measuring changes in basal energy expenditure. The hormonal and inflammatory mediators of hypermetabolism, and the catabolic alterations secondary to hypermetabolism were also examined. Results: Post-burn hypermetabolism was induced in both models of small and large burn. However, large burns resulted in prolonged wound healing, a more pronounced and sustained increase in basal energy expenditure, and a greater stress and systemic inflammatory response with profound catabolic consequences. Conclusions: In the present study, we have successfully characterised the burn induced systemic hypermetabolic response in a mouse model of small and large burn. These models may prove useful for researchers studying the complex aetiology of hypermetabolism and interventions.